Inhibition of SARS CoV Envelope Protein by Flavonoids and Classical Viroporin Inhibitors - Breitinger, Ulrike; Ali, Nourhan K. M.; Sticht, Heinrich; Breitinger, Hans-Georg (Frontiers in Microbiology, 2021)
Severe acute respiratory syndrome coronavirus (SARS-CoV), an enveloped single-stranded positive-sense RNA virus, is a member of the genus Betacorona¬virus, family Coronaviridae. The SARS-CoV envelope protein E is a small (~8.4 kDa) channel-forming membrane protein whose sequence is highly conserved between SARS-CoV and SARS-CoV-2. As a viroporin, it is involved in various aspects of the virus life cycle including assembly, budding, envelope formation, virus release, and inflammasome activation. Here, SARS-CoV E protein was recombinantly expressed in HEK293 cells and channel activity and the effects of viroporin inhibitors studied using patch-clamp electrophysiology and a cell viability assay. We introduced a membrane-directing signal peptide to ensure transfer of recombinant E protein to the plasma membrane. E protein expression induced transmembrane currents that were blocked by various inhibitors. In an ion-reduced buffer system, currents were proton-dependent and blocked by viroporin inhibitors rimantadine and amantadine. I-V relationships of recombinant E protein were not pH-dependent in a classical buffer system with high extracellular Na+ and high intracellular K+. E-protein mediated currents were inhibited by amantadine and rimantadine, as well as HMA. We tested a total of ten flavonoids, finding inhibitory activity of varying potency. Epigallocatechin and quercetin were most effective, with IC50 values of 1.5 ± 0.1 nM and 3.7 ± 0.2 nM, respectively, similar to the potency of rimantadine (IC50 =1.7 ± 0.6 nM). Patch-clamp results were independently verified using a modified cell viability assay for viroporin inhibitors. These results contribute to the development of novel antiviral drugs that suppress virus activity and proliferation.